Influence of computer programs to emergence of extremely situations at industrial object - Семенов, Євгеній Олександрович; Толстоусова, Оксана Валеріївна; Березуцький, Вячеслав Володимирович (Eastern-European Journal of Enterprise Technologies, 2011)
The article devoted to the problem of technogenic emergencies due to failures control of computers in industrial objects, the penetration of to the controlling computer of computer viruses, worms or trojan system programs